Reconnaissance for Radioactive Deposits in Southeastern Alaska, 1952 - Houston, Joseph R.; Bates, Robert Glenn; Velikanje, Robert S.; Wedow, Helmuth, Jr. (United States. Government Printing Office., 1958)
From abstract: Reconnaissance for radioactive deposits in southeastern Alaska in 1952 was centered in three localities: the northern part of Prince of Wales Island and parts of adjacent islands, the Taku Harbor-Point Astley district, and the Hyder area. Significant concentrations of radioactive minerals were found only in the vicinity of Salmon Bay on the northeastern shore of Prince of Wales Island. In this area radioactive carbonate-hematite veins occur along the coast for about 8 miles. The veins are generally short, irregular, and lenticular, but a few can be traced for more than 300 feet between the low-tide line and the forest cover. The width of the veins normally ranges from less than 1 inch to 2.5 feet; several, however, are 5 to 10 feet wide.